2022
DOI: 10.3390/ijms23105755
|View full text |Cite
|
Sign up to set email alerts
|

Application of CRISPR/CasΦ2 System for Genome Editing in Plants

Abstract: CRISPR/Cas system has developed a new technology to modify target genes. In this study, CasΦ2 is a newly Cas protein that we used for genome modification in Arabidopsis and tobacco. PDS and BRI1 of marker genes were chosen for targeting. CasΦ2 has the function to cleave pre-crRNA. In the presence of 10 mM Mg2+ irons concentration, sgRNA3 type guided CasΦ2 to edit target gene and generate mutation, and a mutant seedling of AtBRI1 gene with an expected male sterile phenotype was obtained. In the process of tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In plant genome editing research, the minimal requirement of PAM using CasΦ-2 as shown in the Arabidopsis 8-10 bp deletion of the PDS3 (phytoene desaturase 3) gene suggests a broader editing scope, where there is more flexibility in the target site selection, thereby increasing the chance of generating homozygous or biallelic mutations in plants [142]. Further optimization of the CRISPR-CasΦ-2 in Arabidopsis and tobacco shows promising results in terms of improved genome editing efficiency and specificity, and can be applied to economically important crops for enhancing their traits [145].…”
Section: Class 2 Type V Crispr-casφ Systemsmentioning
confidence: 99%
“…In plant genome editing research, the minimal requirement of PAM using CasΦ-2 as shown in the Arabidopsis 8-10 bp deletion of the PDS3 (phytoene desaturase 3) gene suggests a broader editing scope, where there is more flexibility in the target site selection, thereby increasing the chance of generating homozygous or biallelic mutations in plants [142]. Further optimization of the CRISPR-CasΦ-2 in Arabidopsis and tobacco shows promising results in terms of improved genome editing efficiency and specificity, and can be applied to economically important crops for enhancing their traits [145].…”
Section: Class 2 Type V Crispr-casφ Systemsmentioning
confidence: 99%
“…The concentration of NaCl and MgCl 2 greatly affects the performance of SpCas12f1 and AsCas12f1 in vitro while increased MgCl 2 concentration in the tissue culture medium improved the number of genome-edited T 0 transformants using CRISPR/Cas12j-2 (Cai et al 2022 ). To study the effect of NaCl and MgCl 2 on Cas12j-2, SpCas12f1, CasMINIv3.1 and AsCas12f1 editing efficiency, we selected the most efficient gRNA for each enzyme and evaluated editing efficiency in N. benthamiana leaves using two different concentrations of NaCl (100 mM and 200 mM) and MgCl 2 (60 mM and 110 mM) in the infiltration buffer.…”
mentioning
confidence: 99%